2015
DOI: 10.1007/s11764-015-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship care plan preferences of cancer survivors and health care providers: a systematic review and quality appraisal of the evidence

Abstract: Treatment summaries and survivorship care plans are useful for cancer survivors; however, future rigorous studies should be conducted to identify and prioritize the preferences of survivors regarding these.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 54 publications
(164 reference statements)
3
43
0
1
Order By: Relevance
“…Although survivors reported an overall high level of satisfaction with the ISCP in other studies (Brennan et al, 2014;Klemanski et al, 2015;Stricker et al, 2011), a lack of measurable proof of its added value has also been found (Brennan et al, 2014;Klemanski et al, 2015;Mayer et al, 2014) and the best practices have yet to be validated by research (Stricker & O'Brien, 2014). Despite growing support for ISCP, it is slow to be adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Although survivors reported an overall high level of satisfaction with the ISCP in other studies (Brennan et al, 2014;Klemanski et al, 2015;Stricker et al, 2011), a lack of measurable proof of its added value has also been found (Brennan et al, 2014;Klemanski et al, 2015;Mayer et al, 2014) and the best practices have yet to be validated by research (Stricker & O'Brien, 2014). Despite growing support for ISCP, it is slow to be adopted.…”
Section: Resultsmentioning
confidence: 99%
“…Bien que les survivants rapportent un niveau de satisfaction élevé pour le PSS dans l'ensemble des études (Brennan et al, 2014;Klemanski et al, 2015;Stricker et al, 2011), un manque de preuves mesurables sur sa valeur ajoutée y est associé (Brennan et al, 2014;Klemanski et al, 2015;Mayer et al, 2014) et les meilleures pratiques n'ont pas été validées par la recherche (Stricker et O'Brien, 2014). Malgré le soutien croissant pour le PSS, son adoption est lente.…”
Section: Resultsunclassified
“…While scp research has grown, best practices for patient and provider assessment and scp delivery post-treatment remain unclear or not broadly instituted 2,7,8 . A developing literature supports the use of scps [9][10][11][12][13][14] , and describes optimal content, formats 4,[15][16][17][18][19][20][21][22] , and key-stakeholders' views 1,23,24 , but methods of evaluating scps and their impact on stakeholders are just emerging 4,[25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%